Astrophysical gravitational-wave echoes from galactic nuclei. Issue 3 (22nd July 2022) - Gondán, László; Kocsis, Bence
ABSTRACT: Galactic nuclei (GNs) are dense stellar environments abundant in gravitational-wave (GW) sources for the Laser Interferometer Gravitational-Wave Observatory (LIGO), Virgo, and Kamioka Gravitational Wave Detector (KAGRA). The GWs may be generated by stellar-mass black hole (BH) or neutron star mergers following gravitational bremsstrahlung, dynamical scattering encounters, Kozai–Lidov-type oscillations driven by the central supermassive black hole (SMBH), or gas-assisted mergers if present. In this paper, we examine a smoking gun signature to identify sources in GNs: the GWs scattered by the central SMBH. This produces a secondary signal, an astrophysical GW echo, which has a very similar time–frequency evolution as the primary signal but arrives after a time delay. We determine the amplitude and time-delay distribution of the GW echo as a function of source distance from the SMBH. Between ${\sim} 10{{\ \rm per\ cent}}\hbox{ and }90{{\ \rm per\ cent}}$ of the detectable echoes arrive within ${\sim} (1\hbox{--}100)M_6\, s$ after the primary GW for sources between 10 and 10 4 Schwarzschild radius, where $M_6=M_{{\rm SMBH}, z}/(10^6\, M_{\odot })$, and M SMBH, z is the observer-frame SMBH mass. The echo arrival times are systematically longer for high signal-to-noise ratio (SNR) primary GWs, where the GW echo rays are scattered at large deflection angles. In particular, ${\sim} 10{{\ \rm per\ cent}}\hbox{--}90{{\ \rm per\ cent}}$ of the distribution is shifted to ${\sim} (5\hbox{--}1800)M_6\, s$ for sources, where the lower limit of echo detection is 0.02 of the primary signal amplitude. We find that ${\sim} 5{{\ \rm per\ cent}}\hbox{--}30{{\ \rm per\ cent}}$ (${\sim} 1{{\ \rm per\ cent}}\hbox{--}7{{\ \rm per\ cent}}$ ) of GW sources have an echo amplitude larger than 0.2–0.05 times the amplitude of the primary signal if the source distance from the SMBH is 50 (200) Schwarzschild radius. Non-detections can rule out that a GW source is near an SMBH.